Throat Colonization and Antibiotic Susceptibility of Group a β-Hemolytic Streptococci Among Rheumatic Heart Disease Patients Attending a Cardiac Referral Hospital in Tanzania, a Descriptive Cross-Sectional Study - Wangilisasi, Sarah; Chillo, Pilly; Kimambo, Delilah; Janabi, Mohammed; Kamuhabwa, Appolinary (Frontiers in Surgery, 2020)
Background: Secondary prophylaxis against repeated attacks of acute rheumatic fever is an important intervention in patients with rheumatic heart disease (RHD) and it aims to prevent throat infection by group A beta-hemolytic streptococcus (GAS), however its implementation faces many challenges. This study aimed to assess throat colonization, antibiotic susceptibility and factors associated with GAS colonization among patients with RHD attending care at Jakaya Kikwete Cardiac Institute in Dar-es-Salaam, Tanzania. Methods: A descriptive cross sectional study of RHD patients attending the Jakaya Kikwete Cardiac Institute was conducted from March to May 2018, where we consecutively enrolled all patients known to have RHD and coming for their regular clinic follow-up. A structured questionnaire was used to obtain patients’ socio-demographic information, factors associated with GAS colonization as well as status of secondary prophylaxis use and adherence. Throat swabs were taken and cultured to determine the presence of GAS, and isolates of GAS were tested for antibiotic susceptibility using Kirby-Bauer disk diffusion method according to the Clinical and Laboratory Standards Institute (CLSI) version 2015. Antibiotics of interest were chosen according to the Tanzanian Treatment Guidelines. Results: In total 194 patients with RHD were enrolled, their mean age was 28.4 ±16.5 years and 58.2% were females. Only 58 (29.9%) patients were on regular prophylaxis, 39 (20.1%) had stopped taking prophylaxis, while 97 (50.0%) had never been on prophylaxis. Throat cultures were positive for GAS in 25 (12.9%) patients. Patients who stopped prophylaxis were 3.26 times more likely to be colonized by GAS when compared to patients on regular prophylaxis. Majority (96%) of GAS isolates were susceptible to Penicillin, Ceftriaxone and Ciprofloxacin, while the highest resistance (20%) was observed with Vancomycin. No GAS resistance was observed against Penicillin. Conclusion: The prevalence of GAS throat colonization is high among this population and is associated with stopping prophylaxis. The proportion of patients on regular secondary prophylaxis is unacceptably low and interventions should target both patients’ and physicians’ barriers to effective secondary prophylaxis.